Advancing breast cancer therapy in the era of molecular diagnostics - Maria Grazia Carnevale; Riccardo Ray Colciago; Maria Carmen De Santis; Laura Cortesi; Cinzia De Marco; Antonio Marra; Andrea Vingiani; Franco Nolè; Giuseppe Curigliano; Giancarlo Pruneri; Antonio Llombart-Cussac; Serena Di Cosimo; et al. (Breast)
Advances in cancer biology and drug development now enable treatments tailored to individual tumor profile. Targeting specific molecular alterations marked a significant step forward in cancer care, including breast cancer. Access to these therapies is improving thanks to the implementation of molecular tumor boards and efforts to provide molecular diagnostics at sustainable costs for all. In this context, we highlight recent progress in breast cancer therapy, focusing on biomarker-driven approaches, immunotherapy, and precision medicine paving the way for increasingly personalized and effective options.